The Implementation of SDGs Desa in South Sulawesi (Indonesia) - Kaslam, Kaslam (Review of International Relations, 2024)
SDGs Desa is an integrated effort for global development in the economic, social, environmental, legal and community governance fields at the village level. Village SDGs are derived from the national SDGs targets in 18 development areas. The Village SDGs aim to accelerate the goals of the Sustainable Development Goals by including simplification of goals, localization of targets in villages, and alignment of target indicators. This paper aims to analyze the progress of achieving the SDGs Desa in South Sulawesi, so as to provide an overview of each target that must be improved and maintained. The method used is descriptive quantitative by takin SDGs Desa data for all villages in South Sulawesi, on the website sid.kemendesa.go.id. The results of the study show that in general, South Sulawesi's SDGs Desa fall into the low category with a value of 46.66. Only 1 target is included in the high category, 7 targets are included in the medium category and 10 targets are included in the low category. Thus, the progress of increasing SDGs Desa in South Sulawesi needs to be a concern of the government to immediately improve.